The problems of optimal design in the automotive industry - Dyakov, Ivan (Transport, 2013)
The paper considers the general problems of optimization of parameters of a vehicle at the design stage. The approaches to the solution of the task are set out. The questions of a choice of the objective function and the system of limitations are in focus, as the problem of optimization makes sense, if there are several possible variants of its solution. First Published Online: 11 Oct 2013